2020
DOI: 10.1074/jbc.ra119.011385
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the erythropoietin-producing receptor EPHB4 antagonizes androgen receptor overexpression and reduces enzalutamide resistance

Abstract: Prostate cancer (PCa) cells heavily rely on an active androgen receptor (AR) pathway for their survival. Enzalutamide (MDV3100) is a second-generation antiandrogenic drug that was approved by the Food and Drug Administration in 2012 to treat patients with castration-resistant prostate cancer (CRPC). However, emergence of resistance against this drug is inevitable, and it has been a major challenge to develop interventions that help manage enzalutamide-resistant CRPC. Erythropoietin-producing human hepatocellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Specifically, after binding to EpoR on the surface of erythroid progenitor cells and proto-erythrocytes, Epo can promote cell proliferation and differentiation to form functionally mature red blood cells. Furthermore, Epo promotes capillary formation without weakening the tight junctions between endothelial cells and thus does not increase exudation (12,13). Therefore, Epo and its receptor, EpoR, have gradually attracted attention as independent factors promoting retinal neovascularization (14).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, after binding to EpoR on the surface of erythroid progenitor cells and proto-erythrocytes, Epo can promote cell proliferation and differentiation to form functionally mature red blood cells. Furthermore, Epo promotes capillary formation without weakening the tight junctions between endothelial cells and thus does not increase exudation (12,13). Therefore, Epo and its receptor, EpoR, have gradually attracted attention as independent factors promoting retinal neovascularization (14).…”
Section: Discussionmentioning
confidence: 99%
“…Another cellular pathway involved in AR activation is c-Myc. One study showed induction of c-Myc’s expression by erythropoietin-producing human hepatocellular (Eph) receptors, which is a key factor for enzalutamide resistance [ 28 ].…”
Section: Enzalutamidementioning
confidence: 99%
“…5,7,8,19 AR and AR-Vs are the most frequently aberrant genes found in the development of drug resistance, making them the first-line targets on the clinical treatment. Recently, multiple studies reveal the underlying signaling pathways involved in the acquisition of Enzalutamide resistance, such as Notch1, 41 EPHB4, 42 Wnt/ÎČ-Catenin, 43 noncanonical Wnt, 44 EZH2, 45 and HMGCR. 46 The inhibition of these pathways/molecules could significantly enhance the efficacy of Enzalutamide through cooperative repression on the AR signaling pathway, further emphasizing that targeting AR and AR-Vs is the dominant therapeutic strategy to treat prostate cancer in the clinic.…”
Section: Dip G Enhances the Efficiency Of The Hsp90 Blockadementioning
confidence: 99%